THE INFLUENCE OF MOTIVATION AND DISCIPLINE AGAINST PRODUCTIVITY OF EDUCATIONAL STAFF IN UIN RADEN INTAN LAMPUNG - Heni Noviarita (Saburai International Journal of Social Sciences and Development, 2017)
The influence of motivation and discipline of the Work Productivity of Educational staff in the UIN Raden Intan Lampung This study aims to find out the influence of motivation and discipline of the workplace productivity of educational staffs in the UIN Raden Intan Lampung as well as the partial simultaneously design and research using the survey design in a way to gather information from respondents with the statement (kuisioner) that structured and patterned according to the needs and the title refers to the research and examined the variables that motivation is a variable (X1), variable-disciplinary work (X2) and a variable work productivity (Y). The research was conducted specifically to the educational staffs in the UIN Raden Intan Lampung as many as 71 research respondents. Based on research results obtained significant F value of 0,000 was less than 0.05 level of significance means of discipline and motivation can have a significant effect on the productivity of Educational staffs.The influence that occurred between the motivation and discipline to work simultaneously work productivity (ryxj) with a regression coefficient of 0,681 with a coefficient diterminasinya (r2yxi) of 0.464, or 46.4% variable work productivity is influenced by the motivation and discipline of work. The influence of motivation on the partial work productivity is very significant that this can be seen from the significant value of t the 0,000 amounting to less than 0.05 significance level. Then the influence of the work discipline of the partial work productivity is very significant that this can be seen from the significance of 0,014 earned less than the 0.05 significance level. The conclusions of this study are : 1) work motivation and work diciplinne together to influence on significant to the productivity of education personel at State Islamic University Raden Intan Lampung (2) The influence of the work motivation of the partial work productivity have signeficant effect on labour productivity of labour force in UIN Raden Intan Lampung, (3) The influence of the work discipline of the partial work productivity have signeficant effect on labour productivity of labour force in UIN Raden Intan Lampung